Bridging Tahfidz and Tahsin: A Model for Quranic Literacy in Indonesian Islamic Schools - Ainur Rhain; Andri Nirwana AN; Ahmad Nurrohim; Aulia Naufal; Yeti Dahliana (Walidem Institute and Publishing, 2025)
Objective: This study aims to explore the implementation of tahfidz and tahsin programs at SMP Muhammadiyah 5 Surakarta, as well as identify strategies to improve the quality of memorization and recitation of the Qur'an through the optimization of dormitory facilities and the implementation of Saturday Islamic Boarding School activities (Pesat). Theoretical framework: This research is based on Qur'anic learning theory that emphasizes the integration of tahsin and tahfidz as part of Islamic character education, as well as kinesthetic and repetitive approaches such as talaqqi, tikrār, and muroja'ah to support successful memorization. Literature review: The literature review covers the urgency of tahfidz and tahsin in Islamic education, the effectiveness of methods such as talaqqi and tasmi', the role of curriculum and facilities, and the importance of tahsin as a basis for correct memorization. The literature also discusses common reading errors and their corrective strategies. Methods: The research uses a descriptive qualitative approach with a field study method. Data collection techniques include observation, interviews, and documentation, which are analyzed interactively through reduction, presentation, and conclusions drawn. The validity of the data was tested by triangulation and member check. Result: The results of the study show that the tahfidz and tahsin programs at SMP Muhammadiyah 5 Surakarta have great potential but have not been fully optimized. Two flagship programs were developed, namely the boarding school dormitory program and Pesat (Saturday Islamic Boarding School), which aims to improve the quality and quantity of memorization. It was also found that some students did not have the correct reading skills, so they needed to learn first before entering the tahfidz stage. Implications: This study shows the need for collaboration between schools, teachers, and policymakers in designing the tahfidz-tahsin curriculum and optimizing dormitory facilities to support intensive Qur'an learning. Novelty: This study presents a school-based Qur'an coaching model with the integration of tahsin as a prerequisite for tahfidz, utilizing the boarding system and the Pesat program as effective learning innovations.